Digital Leadership of School Principals in Optimizing Mobile Learning Applications to Improve Literacy in Elementary Schools - Nur Efendi (Gerasi Insan Nusantara, 2024)
This study investigates how digital leadership of school principals optimizes the use of mobile learning applications to improve literacy in elementary education. The research employed a qualitative case study design conducted at MI GUPPI Tasikmadu Watulimo Trenggalek, involving one principal and six teachers selected purposively. Data were collected through semi-structured interviews, classroom observations, and documentation analysis, then analyzed using thematic analysis. The findings indicate that the principal enacted digital leadership through clear vision, structured resource management, and continuous professional support that guided teachers in integrating mobile learning into literacy instruction. Teachers implemented interactive and contextual learning activities using mobile applications for reading, writing, and comprehension tasks. Students demonstrated increased engagement, improved reading comprehension, and stronger writing performance, along with greater motivation in learning activities. The alignment between leadership practices and instructional implementation created a consistent and supportive learning environment. The study concludes that digital leadership significantly contributes to the effectiveness of mobile learning applications in enhancing literacy outcomes in elementary schools.